Analysis of hydrocarbon dispersion film in Casablanca port area - Boanta, D. S (Technium EcoGeoMarine, 2023)
The main focus of this paper is the analysis of the dispersion of hydro screws in the area of Casablanca harbour. In the following I will analyse the evolution of hydrocarbon dispersion according to the parameters: wind and current and their combined action. Subsequently, based on the analysis performed and depending on the amount of hydrocarbon discharged, in the chosen area, I will also choose how to clean the spilled hydrocarbon.